Pengaruh Peran Orang Tua Terhadap Perencanaan Karir Siswa Kelas XII SMA Negeri 1 Pangkal Pinang - Lestari, Paras Aulia (IJoCE: Indonesian Journal of Counseling and Education, 2025)
This study aims to analyze the influence of parental roles on career planning of grade XII students at SMA Negeri 1 Pangkal Pinang. Using a descriptive quantitative method, data were collected through a Likert-based questionnaire distributed to 35 students. The results showed that parental involvement, both in the form of emotional support and career guidance, had a significant positive impact on the maturity of students’ career planning. As many as 75% of students reported that their parents actively supported their career planning, and 80% of students who received emotional support showed clarity in choosing a career path. However, about 40% of students also felt pressure from parental expectations, which could hinder career decision-making that was in line with their interests and abilities. The Pearson correlation test showed a significant positive relationship between parental roles and students’ career planning with a correlation value of 0.484 and a significance of 0.003. These findings emphasize the importance of parental support in the student career planning process and recommend increasing parental involvement in career guidance programs in schools to create an environment that supports students’ career development.